Antitumor activity of Pd(II) complexes with N, S or O, S coordination modes of acylthiourea ligands. (1st July 2020) - Plutín, Ana M.; Ramos, Raúl; Mocelo, Raúl; Alvarez, Anislay; Castellano, Eduardo E.; Cominetti, Marcia R.; Oliveira, Katia M.; Donizeth de Oliveira, Tamires; Silva, Thales E.M.; S. Correa, Rodrigo; Batista, Alzir A.
Graphical abstract: This paper highlights the structural and biological aspects of seven Pd(II) complexes with acylthioureas. Interestingly, we observed that the S, N-chelation mode occurs when monosubstituted acylthioureas are used as ligands, while disubstituted acylthioureas give a S, O-coordination mode to the metal center. Abstract: Seven new complexes (1 –7 ) of Pd(II) with N- alkyl- and N, N -dialkyl- N ′-acylthioureas were prepared and characterized by elemental analysis and spectroscopic techniques. The crystal structures of the coordination compounds [PdCl(PPh3 )( 5- cloropiridyl- N ′-benzoylthioureato-k 2 N, S)] (2 ), cis -[Pd(PPh3 )2 ( N -morpholyn- N ′-benzoylthioureato-k 2 O, S)]PF6 (4 ) and cis -[Pd(PPh3 )2 ( N, N -diphenyl- N ′-thiophenylthioureato-k 2 O, S)]PF6 (7 ) were determined by X-ray crystallography. The present study reports on an interesting contribution on the chemistry of Pd(II)/acylthiourea complexes, where the use of monosubstituted acylthiourea conducts to formation of neutral complexes with general formula [Pd(Cl)(PPh3 )(acylthiourea)], with a N, S-coordination mode. On the other hand, cationic complexes with formula [Pd(PPh3 )2 (acylthiourea)] +, with O, S bidentately coordinated to the metal, are obtained by using a disubstituted acylthiourea derivative. The antitumor activity of the N -alkyl- and N, N -dialkyl- N ′-acylthiourea ligands and their palladium (II) complexes with synthesized triphenylphosphine were evaluated against the growth of the DU-145 tumor cells (prostate cancer cells), (MDA-MB-231 (breast cancer cells), L929 (healthy mouse cells). The ligands are not cytotoxic, but the complexes showed good cytotoxicity against the tumor cells tested in this work, and were even better, when compared to the IC50 reported for the cisplatin. The complexes showed better activity results in MDA-MB-231 tumor cells, than for the DU-145 tumor cells. Complexes 1 and 6 showed high cytotoxic activity at low micromolar concentrations (IC50 = 1.93 ± 0.45, 0.62 ± 0.08 μM) against MDA-MB-231 (human breast cancer cells). This result indicated that the binding of the ligands to the metal center increases their antitumor activity.